2014
DOI: 10.1037/cou0000028
|View full text |Cite
|
Sign up to set email alerts
|

Orienting patient to affect, sense of self, and the activation of affect over the course of psychotherapy with cluster C patients.

Abstract: This article investigates whether patients' sense of self and therapists' interventions aimed at orienting patients toward affect produce an affective activation in the patient. Both the independent contribution of sense of self and therapist intervention, as well as sense of self's moderating effect on therapist interventions, were investigated. Fifty cluster C patients were analyzed using 2 psychotherapy process measures and multilevel modeling. The results indicate that patients' affect experience increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 39 publications
4
35
1
Order By: Relevance
“…The findings with regard to interpretation and encouragement of emotional expression can inform clinical practice and are consistent with psychodynamic mechanisms of change models (Blagys & Hilsenroth, ; Book, ; Fosha, ; Luborsky, ; Luborsky & Crits‐Christoph, ; Luborsky et al, ; Malan, ; McCullough et al, ; Strupp & Binder, ; Wachtel, ), whereby increasing the patient's awareness of internal processes and encouraging expression of affect, lead to general improvement in well‐being. They are also consistent with previous studies showing that techniques aimed at patients achieving better understanding of themselves (Gibbons et al, , ; Levy et al, ), and encouragement of emotional expression in the session (Diener & Hilsenroth, ; Diener et al, ; Fisher et al, ; Lilliengren et al, ; Ulvenes et al, ; Ulvenes et al, ), are related to improvement within a psychodynamic model of treatment. As most patients in this sample exhibited Axis II co‐morbidity (52% personality disorder diagnosis and 24% subclinical features), this increases the generalizability of these findings to naturalistic settings, whereas many studies on the treatment of depression tend to exclude patients with Axis II co‐morbidity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings with regard to interpretation and encouragement of emotional expression can inform clinical practice and are consistent with psychodynamic mechanisms of change models (Blagys & Hilsenroth, ; Book, ; Fosha, ; Luborsky, ; Luborsky & Crits‐Christoph, ; Luborsky et al, ; Malan, ; McCullough et al, ; Strupp & Binder, ; Wachtel, ), whereby increasing the patient's awareness of internal processes and encouraging expression of affect, lead to general improvement in well‐being. They are also consistent with previous studies showing that techniques aimed at patients achieving better understanding of themselves (Gibbons et al, , ; Levy et al, ), and encouragement of emotional expression in the session (Diener & Hilsenroth, ; Diener et al, ; Fisher et al, ; Lilliengren et al, ; Ulvenes et al, ; Ulvenes et al, ), are related to improvement within a psychodynamic model of treatment. As most patients in this sample exhibited Axis II co‐morbidity (52% personality disorder diagnosis and 24% subclinical features), this increases the generalizability of these findings to naturalistic settings, whereas many studies on the treatment of depression tend to exclude patients with Axis II co‐morbidity.…”
Section: Discussionsupporting
confidence: 90%
“…Other work suggests that the contribution of therapists encouraging emotional expression and/or exploration in the session may also vary depending on patient characteristics and treatment modality. Ulvenes et al () examined how therapist's affect orientation in therapy interacted with patients' sense of self to contribute to patients' experience of affect in the session and found that both components were related to experiencing of affect in the session. These findings build off of earlier work by Ulvenes et al () who examined therapist actions, therapeutic bond, and outcome in both dynamic and cognitive therapy and had mixed findings with regard to a focus on affect during the session.…”
mentioning
confidence: 99%
“…CULTURAL HUMILITY IN PSYCHODYNAMIC PSYCHOTHERAPY findings are in line with Ulvenes et al (2014) conjecture that the most important therapeutic processes are at the within-client level.…”
Section: Therapist-state Cultural Humility Across Sessionssupporting
confidence: 84%
“…A limited number of studies have examined the different effects of counselor interventions on client outcomes at different levels of analyses. For example, Ulvenes et al (2014) found that session-to-session variations in therapists’ focus on affect (a between-session or within-client effect), rather than variations in focusing on affect among a therapist’s clients (a between-client or within-counselor effect), was related to clients expressing more affect. Shafran, Kivlighan, Gelso, Bhatia, and Hill (2016) found that at the between-session level, when therapists used more immediacy in a session, clients gave higher session quality ratings for that session.…”
Section: Associations At Different Levels: a Missing Piece In The Litmentioning
confidence: 99%